Description of a new divergent lineage and three new species of Honduran salamanders of the genus Oedipina (Caudata, Plethodontidae) - Mccranie, James R.; Vieites, David R.; Wake, David B. (Zootaxa, 2008)
We describe three new species of the plethodontid salamander genus Oedipina from Honduras. All three are relatively small to moderate sized, elongated and attenuate forms, which are differentiated from each other and from other members of the genus in limb and digital features, size, and body shape. Their distinctiveness is validated by phylogenetic analysis of mtDNA (cytochrome b and 16S) data, which shows each to be strongly differentiated. Furthermore, two of the three species are sister taxa and they comprise a third major clade in the genus, which we recognize as a new subgenus.